Hydraulic Ram Pump / Muhammad Hafiz Haslam Johar, Muhammad Firdaus Syahiran Rosli and Nur’Amirah Hamid - Johar, Muhammad Hafiz Haslam; Rosli, Muhammad Firdaus Syahiran; Hamid, Nur’Amirah (Faculty of Plantation and Agrotechnology, 2023)
A form of energy called hydraulic energy makes use of the flow of water. It is frequently referred to as "water energy," and it allows us to produce electricity by using the kinetic and potential energy from waterfalls and currents. Utilizing the power of streams, rivers, and waterfalls is a clean and sustainable energy source. Typically, hydroelectric power plants atop dams and reservoirs come to mind when we think about hydraulic energy. The most common application of hydraulic energy nowadays is to create electricity. To give us an indication, 17% of the power produced in Spain comes from hydraulic energy plants. The goal of this research is to create a water pump that transports water to higher land using natural hydro energy as the driving force. The only pump that simply uses the kinetic energy of the moving water to pump water is the Hydraulic Ram Pump. The water hammer effect is the main process that enables a hydraulic ram to pump water without the aid of outside energy. Ram pumps do not require electricity since they are powered by the kinetic energy of the falling water. You save energy when you use a ram pump to carry water into your house or farm. Energy conservation increases the amount of money you save on electricity costs. Additionally, conserving power helps protect the environment by halting future pollution